(untitled) (Jurnal Arsitektur ARCADE, 2026)
Coastal reclamation occurs due to the increasing growth rate and the rapidly increasing need for land. Mamuju City is one of the cities experiencing a reclamation process that occurred in its coastal area, then developed into a public space with a variety of social, economic and recreational activities. As this development, this area has emerged various groups of space users, including Gen Z. Currently dominating activities in the area. This phenomenon encourages the importance of understanding Gen Z through their spatial experiences. This study aims to determine how Generation Z views the image of the area as a public space formed by the reclamation process. For Gen Z, public space is not only a place to accommodate activities, but how the place is meaningful and provides a spatial experience. The method used is cognitive mapping, based on Lynch’s theory, namely landmarks, nodes, paths, districts, and edges. The findings show that the more dominant areas are the structure of the city image chosen by respondents. This shows that the area has unique physical elements and meanings given by Generation Z, so that the image of the area is formed from the results of Generation Z’s perceptions as a result of interpretations of the Manakarra Coastal Area.